A study of the role of intervention in the final outcome of acute pancreatitis - Krishnamoorthy, Vengadakrishnan; A. K., Koushik (International Journal of Research in Medical Sciences, 2017)
Background: Acute pancreatitis is a common disease which varies in severity, from mild self-limiting pancreatic inflammation to severe pancreatic necrosis with life-threatening sequelae. As per the recent recommendations early intensive care with delayed intervention and step-up approach when indicated has definite survival advantages over the risks associated with early surgical procedures. The present study was aimed at evaluating the mortality and morbidity risk in patients undergoing procedural intervention in acute pancreatitis. Methods: This was a prospective study done in Sri Ramachandra Medical College and Hospital from April 2012- September 2014. All patients with a diagnosis of acute pancreatitis were included in this study. A total of 110 patients were analysed. Routine lab parameters, serum amylase, lipase, lipid profile, calcium, CRP, LDH, CT abdomen, CXR and 2D Echo was done for all patients. Procedural intervention was planned as per the guidelines. Results: Patients were given early intensive care as per the initial severity scores. 25 patients required intervention. Serum LDH, amylase, lipase and CT severity index were better predictors of requirement of intervention and death. Open necrosectomy was done in 15 patients (13.6%), laparoscopic necrosectomy in 3 patients (2.7%) and step up approach was tried in 7 patients (6.4%). Patients who were tried step up approach were monitored closely for any deterioration in their clinical condition to decide about surgery. 7 out of 8 patients who underwent surgery died. Alcoholic pancreatitis that underwent intervention had a high risk of mortality. Conclusions: Intensive care monitoring with delayed intervention had a better survival benefit. Patients subjected to minimally invasive interventions had a better chance of survival.